The Augustan space: the poetics of geography, topography and monumentality - Gale, Monica R.; Chahoud, Anna (Cambridge University Press, 2024)
Augustus famously boasted that, having inherited a city of brick, he bequeathed a city of marble; but the transformation of the City's physical fabric is only one aspect of a pervasive concern with geography, topography and monumentality that dominates Augustan culture and - in particular - Augustan poetry and poetics. Contributors to the present volume bring a range of approaches to bear on the works of Horace, Virgil, Propertius and Ovid, and explore their construction and representation of Greek, Roman and imperial space; centre and periphery; relations between written monuments and the physical City; movement within, beyond and away from Rome; gendered and heterotopic spaces; and Rome itself, as caput mundi, as cosmopolis and as 'heavenly city'. The introduction considers the wider cultural importance of space and monumentality in first-century Rome, and situates the volume's key themes within the context of the spatial turn in Classical Studies.
Keywords: Rome (Italy) -- In literature; Rome (Italy) -- Buildings, structures, etc; Aufsatzsammlung; Versdichtung; Raum; Monumentalität; Vergilius Maro, Publius; Propertius, Sextus; Ovidius Naso, Publius; Horatius Flaccus, Quintus